(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Extra-curricular sports and health-improving work becomes an integral part of the pedagogical process aimed at educating a comprehensively physically and spiritually developed personality. This is facilitated by the organization and holding of mass sports events.